Improving Employee Performance: An Intervening Model of Organizational Culture on the Influence of Servant Leadership and Employee Engagement - Hafid, Haeruddin; Rahmat, Aswar; Edy, Sri Amalia (Pusat P2M Politeknik Negeri Batam, 2024)
This study investigates the enhancement of employee performance by utilizing an intervening model of organizational culture to examine the effects of servant leadership and employee engagement. Data were collected using a questionnaire from a sample of 41 respondents. Structural equation modeling (SEM) with the partial least squares (PLS) method was employed for data analysis. The analysis included testing both the measurement model (Outer Model) and the structural model (Inner Model). The aim was to assess whether employee performance can be improved through the impact of servant leadership and employee engagement, mediated by organizational culture. The results reveal that servant leadership and employee engagement have a positive and significant effect on organizational culture. Additionally, organizational culture positively and significantly affects employee performance. Servant leadership and employee engagement also directly influence employee performance. Furthermore, servant leadership and employee engagement exert an indirect effect on employee performance through organizational culture.